The effect of a high-pressure protocol on penalty shooting performance, psychological, and psychophysiological response in professional football: A mixed methods study. Issue 1 (2nd January 2022) - Ellis, Louise; Ward, Paul
ABSTRACT: The penalty kick in soccer is arguably one of the most highly visible and high-pressured sporting situations in the world. This study examined the effect of a high-pressure protocol on penalty shooting performance, and the associated psychological and psychophysiological responses to, and perceptions of that protocol. A sequential mixed-method research design was employed wherein the experimental condition consisted of a repeated-measures design with pressure as the within-participants factor (low-pressure, high-pressure). Quantitative data collection was complemented with a semi-structured interview. Twenty professional footballers took part. The Immediate Anxiety Measurement Scale (IAMS) and Pressure Likert-type scale were administered prior to both conditions. The NeXus-10 biofeedback system recorded players' heart rate and respiration rate. Outfield players took five penalty kicks to four targets to the goal, under low and high-pressure. Pressure, cognitive anxiety, and respiration rate significantly increased in the high-pressure condition. After controlling for the level of pressure experienced in the high-pressure condition, bivariate variable error performance significantly increased (i.e., players were more variable in their grouping of shots under stress). Qualitative data indicated the 6-step high-pressure protocol predominantly evoked the distraction mechanism. This research provided first insight into the experiences of professional footballers to a simulated high-pressure penalty protocol.